Så går det till: Organdonation - Nilsson, Christer (Socialmedicinsk tidskrift, 2007)
Här följer en redogörelse för händelseförloppet i samband med en multiorgandonation på Blekingesjukhuset i Karlskrona. Förutom det rent medicinska förloppet presenteras också bemötande/omhändertagande av nästående. Tidpunkter och namn är medvetet förändrade av hänsyn till integriteten för alla involverade. The following is a presentation of the chain of events in connection with a multiorgan donation at the Blekinge Hospital in Karlskrona. Besides the medical procedures are also presented how the donor’s next-of-kin were received and continously informed about the procedure. All dates and names are fictitious in consideration of persons involved. Key words: organ donation, family interview, family consent, certifikation of death, criteria of death.